A combined AFLP-multiplex PCR assay for molecular typing of Escherichia coli strains using variable bacterial interspersed mosaic elements - Horváth, R; Dendis, M; Schlegelová, J; Růzicka, F; Benedík, J (Epidemiology and infection, 2004)
The original method for molecular typing of E. coli strains was developed using the polymorphism in chromosomal sequences of bacterial interspersed mosaic elements (BIMEs) detected by multiplex PCR and analysed by AFLP assay. The applicability of the method in the epidemiology of E. coli was tested on a group of 524 strains of human and veterinary origin. In the studied group 18 different genotypes were detected. Significant differences were found in the frequencies of the genotypes among various groups of strains, suggesting the method could be a promising tool in the epidemiology of E. coli.
Keywords: Cattle; Animals; skot; elektroforéza v agarovém gelu; Oligonucleotide Array Sequence Analysis; Genotype; Escherichia coli Infections; infekce vyvolané Escherichia coli; Escherichia coli; polymerázová řetězová reakce; polymorfismus délky restrikčních fragmentů; Polymerase Chain Reaction; DNA bakterií; DNA Fingerprinting; Time Factors; časové faktory; DNA, Bacterial; intergenová DNA; Gene Frequency; lidé; Molecular Sequence Data; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; genotyp; Interspersed Repetitive Sequences; DNA fingerprinting; frekvence genu; Genetic Variation; Electrophoresis, Agar Gel; Polymorphism, Restriction Fragment Length; molekulární sekvence - údaje; Molecular Epidemiology; Bacterial Typing Techniques; techniky typizace bakterií; rozptýlené repetitivní sekvence; DNA, Intergenic; zvířata; genetická variace; molekulární epidemiologie; Humans